2016
DOI: 10.2174/1389450116666150727114410
|View full text |Cite
|
Sign up to set email alerts
|

Tapping into Mitochondria to Find Novel Targets for Diabetes Complications

Abstract: Mitochondria produce the majority of cellular energy via the "slow burn" of substrates such as glucose, free fatty acids and ketones. In diabetes, altered mitochondrial energetics and substrate utilisation may explain, in part, an organ's susceptibility to complications. This is particularly evident at sites such as the kidney, heart, neurons and retina, which have high energy demands and oxygen consumption rates to meet functional requirements. Within this review we highlight the recent research implicating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It is characterized by hyperglycaemia, albuminuria, the accumulation of extracellular matrix proteins, and glomerular and tubular epithelial hypertrophy, as well as a reduced glomerular filtration rate following an initial period of hyperfiltration 179 . Mitochondrial energetics are altered in diabetic nephropathy owing to increased ROS and hyperglycae-mia 180 , both of which induce changes in the ETC that cause a decrease in ATP production and an increase in apoptosis 180 . In line with these observations, increased fission, mitochondrial fragmentation and reduced levels of PGC1α are all observed in the early stages of diabetes mellitus 181,182 .…”
Section: Mitochondria and Renal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by hyperglycaemia, albuminuria, the accumulation of extracellular matrix proteins, and glomerular and tubular epithelial hypertrophy, as well as a reduced glomerular filtration rate following an initial period of hyperfiltration 179 . Mitochondrial energetics are altered in diabetic nephropathy owing to increased ROS and hyperglycae-mia 180 , both of which induce changes in the ETC that cause a decrease in ATP production and an increase in apoptosis 180 . In line with these observations, increased fission, mitochondrial fragmentation and reduced levels of PGC1α are all observed in the early stages of diabetes mellitus 181,182 .…”
Section: Mitochondria and Renal Diseasesmentioning
confidence: 99%
“…ROS released from the ETC can damage mtDNA, hindering the production of mitochondrial proteins 183 . The hyperglycaemic state was originally thought to cause mitochondrial dysfunction by stimulating the development of hyperpolarized mitochondria, which produce more ATP and release higher levels of superoxide from complexes I and III than healthy mitochondria 180,184,185 . Administration of antioxidants such as vitamin E and vitamin A did not, however, attenuate the complications of patients with diabetes mellitus, suggesting that mitochondrial ROS might not be the primary mediator of mitochondrial dysfunction in diabetic nephropathy 186 .…”
Section: Mitochondria and Renal Diseasesmentioning
confidence: 99%
“…Chronic vascular complications constitute the main cause of morbidity and mortality in patients with type 2 diabetes (T2DM), among them endothelial dysfunction represents one of important primary events . It has been suggested that excess reactive oxygen species (ROS) production and subsequent decrease in vascular bioavailability of nitric oxide (NO) play a causal role in endothelial dysfunction in diabetes …”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been linked to a vast number of disorders ranging from primary mitochondrial disorders such as Leber's Hereditary Optical Neuropathy (LHON) to common diseases associated with mitochondrial dysfunction such as diabetes [1][2][3]. Despite the large numbers of patients that show mitochondrial dysfunction, there are hardly any drugs on the market that aim to target mitochondrial function directly.…”
Section: Introductionmentioning
confidence: 99%
“…LogP was predicted using ChemDraw Professional software (version 16.0, PerkinElmer, Waltham, MA, USA) 2. LogD was predicted using MarvinView software (version 19.25, ChemAxon, Budapest, Hungary) 3. In vitro cytoprotection of HepG2 by 10 μM SCQs against rotenone-induced mitochondrial complex I dysfunction.…”
mentioning
confidence: 99%